Um olhar de alunos reprovados sobre suas trajetórias escolares na Matemática - Deusdete Viana Baião (2017)
The present dissertation aims to identify which aspects present in the speeches of students failed in the sixth grade of Elementary School II indicate their looks on their school trajectories in Mathematics, according to the literature studied. In order to understand the students' perception of their trajectories and their relationships with failure situations in school and in school Mathematics, the researcher relied on theoreticians such as Bernard Charlot, Miguel Arroyo and Emilio Fanfani, who study the determinants of this failure and the profile of the students who have arrived at school in our day. In addition to these authors, studies in the area of Mathematics Education also are focused on what has been determining the failure of several children and young people specifically in this discipline. Data were constructed using various instruments such as field diary, interview, questionnaire and audio recording. The research is qualitative, as it seeks to investigate the phenomena in all their complexity, and the researcher sought to analyze the data very carefully and not interfere in the subjectivity of the subjects involved. In the course of this work, the studies provided the researcher, among other things, to create three categories to be analyzed: the relationship with the other, which was constituted by teachers, colleagues and family; the relation with the place, represented by the school; and, finally, the relationship with mathematical knowledge. This study pointed out that such relationships were inaccurate, truncated, deficient, etc., and, as a result, the School Institution, for not having known in many moments how to deal with these students in the classroom, eventually led them to a trajectory of failure in school, and specifically in Mathematics. The researcher concludes by pointing out that this work has much to contribute, since it deals with a challenging theme for many Brazilian schools, not only those belonging to public networks, but also those of private networks, showing possible ways to be traced by the school institution, together with their teachers, so that their students have a successful trajectory.